2020
DOI: 10.21203/rs.3.rs-77029/v1
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

A Ten Years Retrospective Study of Hysterectomy in Goba Referral Hospital, Bale Zone, South East Ethiopia, Magnitude Indications and Outcomes

Abstract: Background: Hysterectomy is one of the major surgeries performed in clinical practice for commonly encountered diseases of the female genital tract worldwide. Even if Hysterectomy is widely performed surgery in both developed and low income countries little is known about is epidemiology in rural part of develop countries. Especially in developing countries like Ethiopia representative reliable statistics are rarely available on this important aspect of women’s health mainly on its prevalence, indication and o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 8 publications
(9 reference statements)
0
1
0
Order By: Relevance
“…According to the findings of their study, about half of the women received information from doctors prior to having a hysterectomy, and less than half of the women had prior awareness of hysterectomies. On the other hand (Getachew et al ., 2020 ) , who applied their study on hysterectomy in Goba Referral Hospital, Bale Zone, South East Ethiopia who reported that Women want information and guidance on the many types of surgery, potential post-operative challenges, potential hysterectomy complications, and issues with the care and healing process. In order to provide complete nursing care, it is crucial to educate patients about their needs both before and after hysterectomy and to assess how these patients see their femininity.…”
Section: Discussionmentioning
confidence: 99%
“…According to the findings of their study, about half of the women received information from doctors prior to having a hysterectomy, and less than half of the women had prior awareness of hysterectomies. On the other hand (Getachew et al ., 2020 ) , who applied their study on hysterectomy in Goba Referral Hospital, Bale Zone, South East Ethiopia who reported that Women want information and guidance on the many types of surgery, potential post-operative challenges, potential hysterectomy complications, and issues with the care and healing process. In order to provide complete nursing care, it is crucial to educate patients about their needs both before and after hysterectomy and to assess how these patients see their femininity.…”
Section: Discussionmentioning
confidence: 99%